Study of Partial-Phase Steady-State Operation Modes of Phase-Shift Transformer with Hexagonal Circuit and Regulating Autotransformer - Bosneaga V.; Suslov V. (Problems of the Regional Energetics)
The scope of the work was the study of the phase failure operating for the new FACT’s type phase-shifting device, intended for the flexible connection of AC power systems. The mathamatical model has been developed for conducting this study. The device contains the main phase-shifting transformer based on hexagon circuit with additional regulating autotransformer, this creates the possibility of circular regulation of phase shift angle between connected systems. The model includes two 6-winding three-legs transformers, for which two sets of parameters can be independently set based on the data for the short circuit and no-load modes. The data for the direct sequence parameters is usually provided by the transformer manufacturers, and the data for the zero sequence parameters could be obtained upon additional request. As a result of modeling, the vectors of the voltages and currents were obtained in all windings in the investigated modes with supply source phase failure. This makes it possible to analyze the admissibility of such modes and estimate the need for taking special measures of protection against them. It is shown that the voltages on the windings of the main transformer insignificantly depend on the connection mode of the regulating autotransformer, while the pattern of currents distribution in the windings of the main and regulating transformers to a large extent is determined by said connection mode of the autotransformer. The presence of perceptible zero-sequence current flowing through the grounded neutrals of the power supply source and load is noticed. This fact is connected with the release of insignificant magnetic flux from the magnetic circuit in the surrounding space.